Extrinsic dark-pigmentation of the tooth enamel in pediatric dentistry - Camila Menezes Costa Castelo Branco; Mayra Manoella Perez Reis Santos; Lucas Formiga Araújo; Renata Oliveira Guaré; Maria Teresa Botti Rodrigues Santos; Michele Baffi Diniz (Editorial Ciencias Médicas, 2016)
Dark enamel pigments are due to extrinsic staining and associated with aesthetic problems. The objective is to present two cases of children with black extrinsic pigmentation in the tooth enamel, with emphasis on the type of treatment and monitoring. This is a 5-year-old patient of who constantly used ferrous sulfate to treat anemia by iron deficiency, and another 12-year-old patient with type 1 diabetes and dermatomyositis. In the first case, we observed the presence of black extrinsic pigments in the primary teeth and the first permanent molars, especially in the lingual and vestibular part in the cervical region and middle third, together with incipient caries lesions on the occlusal surfaces of molars and active white spots on the first permanent molars. In the second case, there were strange black pigmentation in the cervical region of the smooth surfaces of the primary and permanent teeth. In the first case, the treatment performed was to remove black pigments and polishing the teeth by means of professional prophylaxis and using an abrasive toothpaste containing micro-granules of pumice. There was an improvement in the clinical aspect from the second session and the treatment ended at the fifth session. For the second case, we observed difficulty to remove the pigmented spots in the cervical region, together with the risk of bleeding gums. When the child needed prophylactic antibiotics, we opted for the daily control of the biofilm and it was not removed by professional cleaning, because the patient did not complain about the aesthetic impact. As conclusions, the extrinsic black pigments can be easily observed in children, and despite its aesthetic effect, it does damage oral health. It should be noted that it is unclear how their presence on the tooth surface reduces susceptibility to caries or tooth decay. In addition, the choice of treatment should always be based on the relation risk-benefit for the patient.